UN And Human Rights - Shoxliyeva Dildora (Zien Journals, 2025)
The United Nations (UN) is the largest international organization working to maintain peace, ensure security, and protect human rights. This article analyzes the UN’s role in safeguarding human rights, the significance of the 1948 Universal Declaration of Human Rights, and the content of the International Covenants on Civil and Political Rights. Furthermore, the activities of UN agencies such as UNESCO, UNICEF, and WHO, as well as Uzbekistan’s reforms in ensuring human rights, are discussed. The study evaluates the UN as a key mechanism for promoting global peace and justice through the protection of human rights.
Keywords: United Nations; human rights; Universal Declaration